PENGARUH AKSES PERMODALAN DAN FINANCIAL LITERACY TERHADAP KEBERLANJUTAN UMKM DI KECAMATAN GALANG - Herliana, Yunda; Atika, Atika; Siregar, Saparuddin (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.01.TAHUN.2025, 2025)
This study aims to analyze the effect of access to capital and financial literacy on the sustainability of MSMEs in Galang District, Deli Serdang Regency. The method used is quantitative, with data collection through questionnaires and documentation. The study population consisted of MSMEs in the culinary sector in Galang Sub-district, with a sample of 79 respondents selected using the Slovin technique and proportional random sampling. Data analysis was conducted using multiple linear regression and t-test, with the help of IBM SPSS version 26. The results showed that access to capital has a negative and significant effect on the sustainability of MSMEs, as seen from the sig value of 0.000 which is smaller than 0.05 and t count -3.690 which is greater than t table 1.990. Meanwhile, financial literacy has a positive and significant effect on MSME sustainability, with a sig value of 0.000 and a t-statistic of 5.855 which is greater than the t-table of 1.990. Simultaneously, access to capital and financial literacy also have a significant effect, with an F value of 23.064 which is greater than the F table of 3.12. In conclusion, limited access to capital has a negative impact, while good financial literacy can improve the sustainability of MSMEs in the area